2020
DOI: 10.48550/arxiv.2007.12185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black hole -- galaxy scaling relations in FIRE: the importance of black hole location and mergers

Onur Çatmabacak,
Robert Feldmann,
Daniel Anglés-Alcázar
et al.

Abstract: The co-evolution of supermassive black holes (SMBHs) with their host galaxies remains to be fully explored, especially at high redshift. While often understood as a consequence of self-regulation via AGN feedback, it may also be explained by alternative SMBH accretion models. Here, we expand on previous work by studying the growth of SMBHs with the help of a large suite of cosmological zoom-in simulations (MassiveFIRE) that are part of the Feedback in Realistic Environments (FIRE) project. The growth of SMBHs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 122 publications
(172 reference statements)
0
8
0
Order By: Relevance
“…This transition has been identified in the FIRE simulations for massive (M > 10 10 M ) galaxies at different redshifts (Muratov et al 2015;Anglés-Alcázar et al 2017b,c;Faucher-Giguère 2018;Ma et al 2017a,b) and coincides with the virialization of the inner halo (Stern et al 2020). The early bursty epoch represents yet another qualitatively distinct regime for black hole growth, where sub-grid accretion calculations predict short (∼1 Myr) accretion episodes that can reach or even exceed the Eddington rate fol-lowed by longer periods of inactivity owing to stellar feedback continuously evacuating gas from galactic nuclei (Figure 9, middle panel; Anglés-Alcázar et al 2017c;Çatmabacak et al 2020;Byrne et al in prep.). These early conditions should be investigated in future hyper-refinement simulations.…”
Section: Diversity Of Accretion Phases On Cosmological Timescalesmentioning
confidence: 99%
“…This transition has been identified in the FIRE simulations for massive (M > 10 10 M ) galaxies at different redshifts (Muratov et al 2015;Anglés-Alcázar et al 2017b,c;Faucher-Giguère 2018;Ma et al 2017a,b) and coincides with the virialization of the inner halo (Stern et al 2020). The early bursty epoch represents yet another qualitatively distinct regime for black hole growth, where sub-grid accretion calculations predict short (∼1 Myr) accretion episodes that can reach or even exceed the Eddington rate fol-lowed by longer periods of inactivity owing to stellar feedback continuously evacuating gas from galactic nuclei (Figure 9, middle panel; Anglés-Alcázar et al 2017c;Çatmabacak et al 2020;Byrne et al in prep.). These early conditions should be investigated in future hyper-refinement simulations.…”
Section: Diversity Of Accretion Phases On Cosmological Timescalesmentioning
confidence: 99%
“…The last row shows the range of variation of each parameter; for the cosmological parameters the range of variation is Ωm ∈[0.1 -0.5], σ 8 ∈ [0.6 -1.0]. We emphasize that simulations with stellar feedback strongly suppresses black hole growth in lower mass galaxies (Anglés-Alcázar et al 2017c;C ¸atmabacak et al 2020). Black hole particles are repositioned to the location of the potential minimum within the FoF host group if it is found within a distance < 4×R 0 , where R 0 is the size of the black hole kernel enclosing the nearest 256 gas elements.…”
Section: Simbamentioning
confidence: 99%
“…Intense UV radiation and energetic supernovae associated with massive star formation heat the interstellar medium and potentially induce mass loss from galactic disks (e.g., Hopkins et al 2011Hopkins et al , 2012Li et al 2015Li et al , 2017Kim & Ostriker 2018). Cosmological hydrodynamical simulations, which explore the coevolutionary process of galaxies and SMBHs, have shown that stellar feedback substantially regulates the mass budget in the nuclear regions and suppresses mass feeding to the central BHs (e.g., Dubois et al 2015;Habouzit et al 2017;Anglés-Alcázar et al 2017;Angles-Alcazar et al 2020;Çatmabacak et al 2020). Latif et al (2018) also demonstrated that the combination between stellar and AGN feedback prevents seed BHs from growing to M BH ∼ 10 9 M by z ∼ 6.…”
Section: Stellar Feedbackmentioning
confidence: 99%